2017
DOI: 10.1016/j.jep.2016.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine for pulmonary fibrosis therapy: Progress and future prospects

Abstract: These research work have shown the therapeutic benefits of TCM in the treatment of PF. However, more continued researches should be undertaken to clarify the unconfirmed chemical composition and regulatory mechanisms, conduct standard clinical trials, and evaluate the possible side effects. The insights provided in present review will be needed for further exploration of botanical drugs in the development of PF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 135 publications
0
84
0
Order By: Relevance
“…Recent studies indicated tanshinone IIA may have potent anti-fibrotic effects on the pathological fibrosis process in different organs [19][20][21]. It has been reported that a tanshinone IIA-containing capsule can alleviate the myocardial fibrosis caused by streptozocin-induced diabetes in rats with high a fat-diet [8], probably by inhibiting the proliferation of cardiac fibroblasts [5], and by reducing the production of extracellular matrix proteins [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated tanshinone IIA may have potent anti-fibrotic effects on the pathological fibrosis process in different organs [19][20][21]. It has been reported that a tanshinone IIA-containing capsule can alleviate the myocardial fibrosis caused by streptozocin-induced diabetes in rats with high a fat-diet [8], probably by inhibiting the proliferation of cardiac fibroblasts [5], and by reducing the production of extracellular matrix proteins [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the data collected by National Health Commission of the People's Republic of China, clinical practice in Chinese hospitals has reported that TCMs have definite therapeutic actions at the early stage of disease , while common antiviral drugs such as oseltamivir, Arbidol and Lopinavir/Ritonavir failed to cure these patients (Cao et al, 2020). As the main component of the medical practice, TCM has been used for more than 5000 years in China in treating human diseases (Li & Kan, 2017). It is a natural chemical library which leads to synergistic actions through multiple mechanisms.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…It also possesses antimicrobial, cytotoxic, larvicidal and antioxidant properties (Cherdtrakulkiat et al . ; Dass & Mariappan ; Li & Kan ).…”
Section: Introductionmentioning
confidence: 99%